Perilaku Pencarian Informasi dengan Menggunakan Portal Jurnal Elektronik “ScienceDirect” dalam Pemenuhan Kebutuhan Informasi Mahasiswa - Adelia Nur Annisa Ritonga (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
This research discusses "Information Search Behavior Using the Electronic Journal Portal "ScienceDirect" in Fulfilling Student Information Needs". The subject matter of this research is the information search behavior of students of the Library Science Study Program at the State Islamic University of North Sumatra. This type of research uses descriptive methods, with a qualitative research approach. This approach aims to identify information search behavior using ScienceDirect Information search behavior using the ScienceDirect electronic journal portal has conducted searches using the stages put forward by Ellis. The results showed that the purpose of information searchers using ScienceDirect was to find references in completing coursework and looking for journals only as reading material. The information sought is articles related to courses majoring in library science and looking for scientific papers on losing weight. In Ellis' theory, there are 8 stages that are passed in the information search process, namely, starting, chaining, browsing, differenting, monitoring, extracting, verifying, and ending. From the analysis, it can be concluded that all informants go through these 8 stages to get the information they need. Some of the differences between using ScienceDirect and using other portals: (a) Availability of articles (sometimes in ScienceDirect not in other portals, and vice versa) (b) Articles obtained are in English, other portals use Indonesian (c) Provides scientific papers from international authorized authors Some obstacles in searching for information using ScienceDirect electronic journals: (a) The articles searched are not very complete (b) Articles in English (c) Network constraints (d) Many paid articles (e) Having to register Many articles are paid (e) Must register for an account (f) Search settings are not easy.